Lactobacillus rhamnosus GG supernatant promotes intestinal barrier function, balances Treg and TH17 cells and ameliorates hepatic injury in a mouse model of chronic-binge alcohol feeding. (22nd January 2016) - Chen, Rui-Cong; Xu, Lan-Man; Du, Shan-Jie; Huang, Si-Si; Wu, He; Dong, Jia-Jia; Huang, Jian-Rong; Wang, Xiao-Dong; Feng, Wen-Ke; Chen, Yong-Ping
Highlights: LGG supernatant ameliorates experimental ALD in a chronic-binge alcohol exposure model. LGG supernatant normalizes the balance of Treg and TH 17 in peripheral blood of mice exposed to chronic-binge alcohol. LGG supernatant decreases the serum level of IL-17 in chronic-binge alcohol mice model. Abstract: Impaired intestinal barrier function plays a critical role in alcohol-induced hepatic injury, and the subsequent excessive absorbed endotoxin and bacterial translocation activate the immune response that aggravates the liver injury. Lactobacillus rhamnosus GG supernatant (LGG-s) has been suggested to improve intestinal barrier function and alleviate the liver injury induced by chronic and binge alcohol consumption, but the underlying mechanisms are still not clear. In this study, chronic-binge alcohol fed model was used to determine the effects of LGG-s on the prevention of alcoholic liver disease in C57BL/6 mice and investigate underlying mechanisms. Mice were fed Lieber–DeCarli diet containing 5% alcohol for 10 days, and one dose of alcohol was gavaged on Day 11. In one group, LGG-s was supplemented along with alcohol. Control mice were fed isocaloric diet. Nine hours later the mice were sacrificed for analysis. Chronic-binge alcohol exposure induced an elevation in liver enzymes, steatosis and morphology changes, while LGG-s supplementation attenuated these changes. Treatment with LGG-s significantly improved intestinal barrier function reflected by increased mRNA expression of tight junction (TJ) proteins and villus-crypt histology in ileum, and decreased Escherichia coli (E. coli ) protein level in liver. Importantly, flow cytometry analysis showed that alcohol reduced Treg cell population while increased TH 17 cell population as well as IL-17 secretion, which was reversed by LGG-s administration. In conclusion, our findings indicate that LGG-s is effective in preventing chronic-binge alcohol exposure-induced liver injury and shed a light on the importance of the balance of Treg and TH 17 cells in the role of LGG-s application.